Green Marketing dalam Industri Running: Persepsi Peserta terhadap Event Lari Berkelanjutan - Riu, Isma Azis (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze participants' perceptions of green marketing practices in sustainable running events, focusing on factors influencing their acceptance and skepticism. Using a phenomenological qualitative approach, data were collected from 20 active runners in Indonesia through in-depth interviews and focus group discussions (FGDs). The findings reveal that transparency of information particularly through external certifications and visual evidence is critical in building participant trust. Seventy percent (70%) of participants were willing to pay higher fees for sustainable events, provided fund allocation was clear and facilities were not compromised. However, 55% of respondents doubted green claims lacking concrete evidence, reflecting persistent risks of greenwashing. Community involvement in post-event activities (tree planting) enhanced participant loyalty, while generational and geographic differences influenced preferences regarding the complexity of green practices. These findings confirm that green marketing strategies in the running industry must integrate credibility, participatory engagement, and pragmatic solutions adaptable to socio-cultural contexts. The study recommends that event organizers design authentic communication models and collaborative programs to strengthen ecological impact and participant satisfaction.